Methodological perspectives of evaluation of cultural heritage in the context of changing scientific paradigms - Petrušonis, Vytautas (Journal of Architecture and Urbanism, 2012)
The situation when objects of cultural heritage are evaluated and interpreted on the basis of denotative knowledge without taking into account additional connotative and broader background information regarding the cultural context, witnesses a crisis of methodology. This crisis is related with a crisis of mentality in the phase of industrial civilisation. To Lithuania’s disadvantage, the most important concern of cultural heritage assessment methodology is that objects ignore the context, while the cultural heritage protection process is inflexible and unable to find common ground with processes of environmental renewal and urban renovation. Such cultural heritage assessment methodology represents ideologies of so called classical and non-classical scientific paradigms. The renovation of cultural heritage assessment methodology could be achieved only when methodological advantages and conceptual possibilities of the so called post-non-classical paradigm would be taken into account. Only then it would be possible to coordinate both protection of cultural heritage as well as creative activity of architects in the field of contemporary architecture while making architectural designs for historically developed cities. The main features of the post-non-classical paradigm can be disclosed: new modes of social communication, knowledge generation and use of the informational technologies, taking into account the context of globalisation. Article in Lithuanian. Kultūros paveldo vertinimo metodologinės perspektyvos bendrųjų mokslinių paradigmų kaitos kontekste Santrauka. Svarbiausias kultūros paveldo vertinimo metodologijos trūkumas yra tai, kad objektai vertinami ignoruojant tapsmo kontekstą, todėl kultūros paveldo apsaugos procesas yra nelankstus, negali rasti sąlyčio su aplinkos atnaujinimo, urbanistinio renovavimo, naujos architektūros kūrimo procesais. Toks kultūros paveldo vertinimo metodologijos būvis yra nulemtas atotrūkio nuo bendrųjų mokslinių metodologinių principų kaitos proceso, yra „užsikonservavęs“ klasikinio ir neklasikinio mokslo idėjų lauke. Tam, kad kultūros paveldo vertinimo metodologija galėtų atsinaujinti ir adekvačiai spręsti kultūros paveldo apsaugos tiek strateginius, tiek taktinius uždavinius ir kartu neblokuoti inovacinių procesų architektūros ir urbanistikos lauke, būtina iš esmės persvarstyti kultūros paveldo apsaugos metodinius principus. Taikant kultūros paveldo vertinimo metodologiją, turi būti įvertintos jos nuostatos orientuojantis į postneklasikiniame mokslinės raidos etape išryškėjusias socialinės komunikacijos, žinių generavimo ir jų panaudojimo praktinėms problemoms spręsti informacinės visuomenės ir globalizacijos sąlygomis galimybes. Reikšminiai žodžiai: kultūros paveldo vertinimo metodologijos krizė, naujos architektūros kūrimas, bendrųjų mokslinių paradigmų kaita, postneklasikinio mokslo raidos etapo teikiamos galimybės.